2005
DOI: 10.1007/bf02760587
|View full text |Cite|
|
Sign up to set email alerts
|

Invasive colonic mucormycosis in early induction therapy of childhood acute lymphoblastic leukemia

Abstract: Fungal infections occur in patients who are severely immunocompromised with profound and prolonged neutropenia. We report a patient of acute lymphoblastic leukemia who developed nonspecific abdominal symptoms within two days after the onset of neutropenia in the early induction phase of chemotherapy, which was later found to be due to intestinal mucormycosis and resulted in a fatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Furthermore, the infecting dose was likely to be rather substantial, because in at least two of our cases (cases 1 and 2), the onset of invasive diseases occurred immediately after the first cycle of induction chemotherapy for acute leukemia. This phenomenon was also shown in a recent case report (40). Since the duration of the neutropenic phase was less than 2 weeks in our cases (cases 1 and 2), the risk of invasive fungal infection should not have been high unless there was a significant load of microbial exposure (14).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the infecting dose was likely to be rather substantial, because in at least two of our cases (cases 1 and 2), the onset of invasive diseases occurred immediately after the first cycle of induction chemotherapy for acute leukemia. This phenomenon was also shown in a recent case report (40). Since the duration of the neutropenic phase was less than 2 weeks in our cases (cases 1 and 2), the risk of invasive fungal infection should not have been high unless there was a significant load of microbial exposure (14).…”
Section: Discussionsupporting
confidence: 86%
“…Mucormycosis can involve any part of the digestive tract [59,160,[258][259][260][261][262][263][264][265][266][267][268][269][270][271][272][273][274][275][276][277], with a mortality rate of 98% according to a published series of 25 accumulated cases [59].…”
Section: O T H E R C L I N I C a L M A N I F E S T A T I O N Smentioning
confidence: 99%
“…Mucormycosis can involve any part of the digestive tract [59,160,258–277], with a mortality rate of 98% according to a published series of 25 accumulated cases [59].…”
Section: Other Clinical Manifestationsmentioning
confidence: 99%
“…Vadeboncoeur et al described a fatal small intestinal mucormycosis in a 31-month-old boy with large cell anaplastic lymphoma early after chemotherapy presented with a gangrenous ileo-ileal intussusception [ 16 ]. Sellappan et al reported a colonic mucormycosis in a 10-year-old male child with Down's syndrome and B-precursor-ALL during induction chemotherapy with a fatal outcome [ 17 ]. Totadri et al described a fatal small intestinal mucormycosis in a 10-year-old male child with B-precursor-ALL during the consolidation phase of chemotherapy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%